2014
DOI: 10.1177/1362168814559802
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of assisted repeated reading techniques for the incidental acquisition of novel foreign vocabulary

Abstract: Although repeated reading – a pedagogical practice often involving phonological support in which learners revisit novel forms in context – has been extensively studied in terms of reading fluency and comprehension, little research has explored whether it promotes language acquisition. The current study, an attempt to fill this gap, found that without explicit instruction 80 Mandarin-speaking intermediate learners of Japanese as a foreign language were capable of recognizing nearly one novel foreign orthographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
2
17
1
Order By: Relevance
“…Even when the focus of assisted repeated reading was on comprehension, students in both groups were able to learn vocabulary. This result is consistent with previous studies showing incidental vocabulary acquisition through assisted repeated reading (Liu & Todd, ; Webb & Chang, ). However, one limitation of this study was that there was no control group, and there could have been a test–retest effect.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Even when the focus of assisted repeated reading was on comprehension, students in both groups were able to learn vocabulary. This result is consistent with previous studies showing incidental vocabulary acquisition through assisted repeated reading (Liu & Todd, ; Webb & Chang, ). However, one limitation of this study was that there was no control group, and there could have been a test–retest effect.…”
Section: Discussionsupporting
confidence: 93%
“…We cannot claim, however, that vocabulary gains were exclusively due to assisted repeated reading. It also has to be noted that the comprehension activities used in the study may also have contributed to a certain level of learning, but it is hard to avoid the use of such activities if we want to ensure comprehension (Liu & Todd, ; Webb & Chang, ) or to promote exposure to the target words in a nonexplicit form. Another potential factor that could have affected learning is how often students read the words or checked the glossary (which had to be provided because of the high rate of unknown words in the text).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study, along with several other studies (e.g., Tian & Macaro, 2012), suggest that intentional FFI is superior to incidental vocabulary exposure in classroom contexts. However, note that a number of studies have shown that a limited amount of vocabulary can also be learned incidentally (e.g., Bisson, van Heuven, Conklin, & Tunney, 2014;Gablasova, 2014;Liu & Todd, 2016;Newton, 2013;Pellicer-Sánchez, 2016).…”
Section: Form-focused Instructionmentioning
confidence: 99%